Determination of Iridotrabecular Contact Using the Anterior Segment Optical Coherence Tomography in Lights-on and Lights-off Conditions - James Paul S. Gomez, MD, DPBO; Edgar U. Leuenberger, MD, DPBO (Philippine Journal of Ophthalmology)
Objective: To determine the presence of iridotrabecular contact (ITC) and compare the changes in anterior chamber angle (ACA) measurements in room lights-on and lights-off conditions using the anterior segment optical coherence tomography (AS-OCT) in eyes diagnosed as primary angle closure suspects (PACS) by gonioscopy.